The impact of climate variability on smallholder farmers in Zimbabwe: a case of Makoni district, Ward 9 (2000-2012) - Mudondo, Tracy Chipo (Midlands State University, 2017)
The study explores the impact of climate variability on smallholder farmers in Makoni District and in order to gain full appreciation of the problem, the study zeroed down to Ward 9. The research juxtaposed qualitative and quantitative methodologies because the researcher saw the need to refer to statistic and numeric data in form of quantifiable responses whilst on the other hand the research largely aimed at revealing and unearthing perceptions, attitudes, beliefs and opinions of respondents pertaining climate variability. This article argues that, climate variability is making it extremely difficult for smallholder farmers to invest in their agricultural activities. The findings shows that, climate variability is a reality in Makoni and reported late and unpredictable rains resulting in seasonal variations in rainfall timing, poor distribution of rainfall within seasons, increases in temperatures, successive and prolonged dry spells and increased frequency in droughts occurrence. It emerged in the study that, weather vagaries resulting from climate variability have caused extensive crop failures, deaths of livestock and low crop output. The study highlighted that, all these have compounded the vulnerability of smallholder farmers by dramatically reversing the poverty reducing capacity of agriculture thereby slowly but surely eroding the source of livelihoods for smallholder farmers. The study however established that, Smallholder Farmers should not remain as passive victims to climate variability related hazards; they should rather devise adaptation mechanisms to cushion the impacts of climatic related risks.